MENINGKATKAN EFETIFITAS PENGGUNAAN ABSENSI DIGITAL DALAM REKAPITULASI GURU DI SEKOLAH DASAR (SD) DESA TREBUNGAN - Azizah, Nur; Jannah, Raudatul; Sudur, Miftahus; Rahman, Zainur; Muhammad, Jagad (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
One important factor to determine the discipline of a student is to record student attendance. The attendance system that has been used so far is to call the student's name then record his attendance on paper, this manual technique causes various problems, for example, it takes a long time to record data, attendance records are damaged due to tearing and various other conditions. In addition, the attendance system that has been running so far has not been able to accurately record student attendance, such as whether students arrive on time or not. Now digital attendance based on the Scan It To Office application overcomes the problems so far. This digital attendance system not only facilitates the attendance process but also helps teachers in recording student attendance. The system device works accurately by using the QR-Code Scan method with a perfect level of accuracy. Translated with DeepL.com (free version)